2014
DOI: 10.1051/0004-6361/201424349
|View full text |Cite
|
Sign up to set email alerts
|

[C II] absorption and emission in the diffuse interstellar medium across the Galactic plane

Abstract: Aims. Ionized carbon is the main gas-phase reservoir of carbon in the neutral diffuse interstellar medium (ISM) and its 158 μm fine structure transition [C ii] is the most important cooling line of the diffuse ISM. We combine [C ii] absorption and emission spectroscopy to gain an improved understanding of physical conditions in the different phases of the ISM.Methods. We present high-resolution [C ii] spectra obtained with the Herschel/HIFI instrument towards bright dust continuum regions in the Galactic plane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 68 publications
(100 reference statements)
12
121
2
Order By: Relevance
“…Gerin et al (2015) found no Galactic gradient in N(C + )/N(H) when N(H 2 ) was derived from N(CH), but this could also be the case when the molecular fraction is high and the abundances of CH and C + scale in the same way with the local metallicity. The discussion is further complicated by the fact that the relevant quantities are the free gas phase abundances after depletion, whereas the Galactic gradient is measured on the metallicity itself.…”
Section: Galactic Metallicity Gradientmentioning
confidence: 89%
See 4 more Smart Citations
“…Gerin et al (2015) found no Galactic gradient in N(C + )/N(H) when N(H 2 ) was derived from N(CH), but this could also be the case when the molecular fraction is high and the abundances of CH and C + scale in the same way with the local metallicity. The discussion is further complicated by the fact that the relevant quantities are the free gas phase abundances after depletion, whereas the Galactic gradient is measured on the metallicity itself.…”
Section: Galactic Metallicity Gradientmentioning
confidence: 89%
“…The in situ number densities and kinetic temperatures measured in C II by Gerin et al (2015) toward W31 were n(H) = 40−45 cm −3 and T K = 90−105 K, presumably a weighted average of the molecular component at n(H) ≈ 135 cm −3 and a less dense, somewhat warmer atomic component. The thermal pressure toward W 31 fell in a narrow range about p/k = n T K = 4000 cm −3 K, implying n(H I) ≈ 30 cm −3 at the temperature T K = 135 K that we used to derive the mean H I density in Fig.…”
Section: In Situ Number Density Of Atomic Gasmentioning
confidence: 91%
See 3 more Smart Citations